Effects of Passive Finger Movement on Cortical Excitability - Nakagawa, Masaki; Sasaki, Ryoki; Tsuiki, Shota; Miyaguchi, Shota; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Onishi, Hideaki (Frontiers in Human Neuroscience, 2017)
This study examined the effects of joint angle and passive movement direction on corticospinal excitability. Motor evoked potentials (MEPs), F-waves, and M-waves were measured during passive adduction and abduction (80°/s) of the right index finger from 14 healthy adults. In Experiment 1, we measured MEP amplitude, F-wave amplitude and persistence, and M-wave amplitude sequentially at static 0° joint angle (neutral), 0° during passive adduction from 10° abduction to 30° adduction (AB10°–AD30°), AD20° during passive adduction (AB10°–AD30°), AD20° during passive reciprocal abduction (AD30°–AB10°), and 0° during passive abduction (AD30°–AB10°). In Experiment 2, MEPs were measured at static 0°, AD20° during passive adduction from AD10° to AD30°, and static AD20°. MEPs were recorded from the right first dorsal interosseous muscle in response to transcranial magnetic stimulation (TMS). Experiment 1 revealed significantly increased MEP amplitude at 0° during passive adduction compared with static 0° (p < 0.01). No other significant differences in MEP, M-wave, and F-wave parameters were observed. In Experiment 2, MEP amplitude was significantly higher at AD20° during passive adduction compared with static 0° (p < 0.01). Thus, MEP facilitation occurred at AD20° during passive movement from AD10° (125 ms delay, Experiment 2) but not AB10° (375 ms delay, Experiment 1). MEP amplitude was not influenced by absolute joint angle, passive movement direction, or spinal excitability. Rather, it may be regulated by changes in intracortical excitability according to afferent input timing, and in this case, intracortical afferent facilitation (AF) from afferent input at movement initiation during the AF temporal window.